A Rare Case of Pituitary Melanoma Metastasis: A Dramatic and Prolonged Response to Dabrafenib-Trametinib Therapy - Mormando, Marilda; Puliani, Giulia; Barnabei, Agnese; Lauretta, Rosa; Bianchini, Marta; Chiefari, Alfonsina; Russillo, Michelangelo; Cognetti, Francesco; Romano, Luisa; Appetecchia, Marialuisa (Frontiers in Endocrinology, 2020)
Introduction: Pituitary metastases (PM) are rare events and only very few cases of melanoma PM are described in literature up to now. Case presentation: we describe the clinical history of a 33-year-old male patient who underwent surgical excision of inter-scapular melanoma in 2008. The subsequent follow up was negative for about 10 years. In September 2018, due to the onset of a severe headache, the patient underwent a brain magnetic resonance imaging that showed an expansive mass in the saddle and suprasellar region with a maximum diameter of 17 mm. Pituitary function tests and visual field were normal. The worsening of the headache and the appearance of a left eye ptosis led the patient, in October 2018, to surgical removal of the lesion.The histological examination showed, unexpectedly, a melanoma metastasis. Postoperative hormonal assessment showed a secondary hypothyroidism and hypoadrenalism, both promptly treated, and a mild hypogonadism. Three months after surgery, a sellar MRI showed a persistent,increased pituitary mass (3 cmof diameter) and a fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) detected an increased radiopharmaceutical uptake in the sellar region. Due to the persistence of the disease and the evidence of a BRAF V600 mutation, in February 2019 patient underwent a combined treatment with dabrafenib (a BRAF inhibitor, BRAFi) and trametinib (mitogen-activated extracellular signal-regulate kinase, MEK inhibitor). Sellar MRI performed 6 months later showed no evidence of mass inthe sellar region. The patient was in good clinical condition and did not complain of headache or other symptoms; there were no significant side effects of anticancer therapy. After 13 months of treatment, the patient showed no recurrence of the disease on morphological imaging.Anticancer therapy was confirmed, replacement therapies with hydrocortisone and levothyroxine continued and the pituitary-gonadal axis was restored. Conclusion:This is a very interesting case, both for the rarity of the pituitary melanoma metastasis and for the singular therapeutic course carried out by the patient. This is the first case of a pituitary melanoma metastasis with BRAF mutation, successfully treated with the combination of dabrafenib and trametinib after incomplete surgical removal.